Partial Independence Beats Full Independence. Issue 3 (2nd July 2016) - Rezvani, David A.
Abstract: It is widely believed that fully independent sovereign states are peerless and preeminent. They are viewed as the ultimate political system for producing economic and security advantages. It is also widely believed that they are the only constitutive unit in the international system that possesses territorial sovereignty. As distinct from these views, this paper will provide theoretical and empirical support to argue in favour of the existence and relative advantages of partially independent territories (PITs). PITs tend to deliver degrees of public goods, nationalistic reconciliation, and credible commitment advantages that sovereign states often cannot provide. The result is that PITs tend to have higher degrees of wealth and security as compared to their sovereign state counterparts. The advantages and widespread existence of PITs amend assumptions about the structure of the Westphalian international system in which sovereign statehood is viewed as exclusive and unchallenged.